Pengaruh Quick Ratio , Debt To Equity Ratio, Total Asset Turnover Terhadap Harga Saham - pamela, yovani melin camelita; Nyale, M. Hendri Yan (Universitas Muhammadiyah Metro, 2023)
This research aims to examine the influence of the Quick Ratio (QR), Debt to Equity Ratio (DER) and Total Asset Turnover (TATO) on stock prices. The model used in the research is a causality research design with quantitative data or secondary data. The population in this research uses companies in the property and real estate sub-sector that are listed on the Indonesia Stock Exchange (BEI) in 2017-2021. The sample selection process used a purposive sampling method, resulting in 100 observation data obtained from 20 companies selected as samples for 5 years of research. The independent variable QR uses the formula current assets minus inventory divided by current liabilities, DER uses the formula total debt divided by equity and TATO uses the formula sales divided by total assets. The dependent variable stock price is taken using the closing price value as of May 31. Hypothesis testing was carried out using a multiple linear regression analysis model using SPSS software. The results of this research show that QR has a positive effect on stock prices, while DER has a negative effect on stock prices. Furthermore, TATO has a positive effect on share prices.